Interoperability of standards and models in official statistics - Poljičak, Martina; Stančić, Hrvoje; Seljan, Sanja (2014)
In Croatian Central Bureau of Statistics (CBS) an Integrated Statistical Information System (ISIS) is built using in its core Croatian Statistical Metadata Repository (CROMETA). ISIS is a multilingual platform intended for generic approach to various statistical surveys using standardized processes for producing standardized statistical outputs. An analysis of the development designs, tools and underlying standards used in projects for development of ISIS will be presented. Also, authors will present the current state of usage of ISIS and analyze the possibility of aligning CBS’ ISIS with currently emerging standards in official statistics.
MZOS, potpora 1 - Sveučilište u Zagrebu
Projekt MZOS
Projekt MZOS
ENG